Gold Nanoparticles: Synthesis, Stability Test, and Application for the Rice Growth. (2nd September 2014) - Wang, Aiwu; Ng, Hoi Pong; Xu, Yi; Li, Yuyu; Zheng, Yuhong; Yu, Jingping; Han, Fugui; Peng, Feng; Fu, Li
Abstract : In today's science, with the use of nanotechnology, nanomaterials, which behave very differently from the bulk solid, can be made. One of the capable uses of nanomaterials is bioapplications which make good use of the specific properties of nanoparticles. However, since the nanoparticles will be used both in-vivo and in-vitro, their stability is an important issue to the scientists, concern. In this dissertation, we are going to test the stability of gold nanoparticles in a number of media including the biocompatible medium and their behaviors will be illustrated in terms of optical properties change and aggregation degree. Herein, we report the synthesis of gold nanoparticles of different shapes and applications for the rice growth with significant difference. The gold nanoparticles can inhibit the elongation of rice root without inhibiting the germination of rice seeds.